2022
DOI: 10.1039/d1ra08763k
|View full text |Cite
|
Sign up to set email alerts
|

Diverse and efficient catalytic applications of new cockscomb flower-like Fe3O4@SiO2@KCC-1@MPTMS@CuIImesoporous nanocomposite in the environmentally benign reduction and reductive acetylation of nitroarenes and one-pot synthesis of some coumarin compounds

Abstract: Herein, a new cockscomb flower-like Fe3O4@SiO2@KCC-1@MPTMS@CuII mesoporous nanocomposite was synthesized, characterized, and used in the green reduction and reductive acetylation of nitroarenes and one-pot synthesis of some coumarin compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 196 publications
0
6
0
Order By: Relevance
“…The DTA curve showed a small endothermic peak at the initial stage, which is due to the removal of water molecules in the material, and a large endothermic peak at around 800 degrees, which is due to thermal degradation. 29 , 30 In addition, the pH stability and iron release of UPBNPs-MCSNs were examined. The pH values of UPBNPs-MCSNs ranged from 9.7 to 9.5 within 270 mins, which was alkaline and decreased slightly with increasing time ( Figure 1M ).…”
Section: Resultsmentioning
confidence: 99%
“…The DTA curve showed a small endothermic peak at the initial stage, which is due to the removal of water molecules in the material, and a large endothermic peak at around 800 degrees, which is due to thermal degradation. 29 , 30 In addition, the pH stability and iron release of UPBNPs-MCSNs were examined. The pH values of UPBNPs-MCSNs ranged from 9.7 to 9.5 within 270 mins, which was alkaline and decreased slightly with increasing time ( Figure 1M ).…”
Section: Resultsmentioning
confidence: 99%
“…Mousavi et al reported the synthesis of coumarins catalysed by cockscomb flower-like nanocomposites (Fe 3 O 4 @SiO 2 @KCC@MPTMS@Cu II ; Scheme 43) 96 1.…”
Section: Scheme 39 Hydrogenation Of 133 To Give 134mentioning
confidence: 99%
“…As tabulated, the synthetic process of DHPMs was accomplished to both electron-donating and electron-withdrawing groups, which led to giving the desired compounds 4a-h in 91-98% yields, and the offered protocol is comprehensive (Table 2). The reaction for the synthesis of DHPMs is controlled by TLC, and the resulting products from this reaction were analyzed by 1 H and 13 C NMR and FT-IR spectrophotometers (Supporting Information S1).…”
Section: Tem Analysismentioning
confidence: 99%
“…Due to their amazing capabilities, magnetic iron oxide nanoparticles have been used frequently in these types as the major component of the core in the core-shell system. 12,13 Metal-organic frameworks (MOFs) comprise highly porous components with clusters connected by organic ligands or inorganic ions. 14,15 In recent years, various applications such as ionic conductivity measurement, drug delivery with the help of porosity, gas storage, separation, and the surface area of materials have been considered.…”
Section: Introductionmentioning
confidence: 99%